1997
DOI: 10.1095/biolreprod56.2.523
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting in Vitro Maturation of Minke Whale (Balaenoptera acutorostrata) Follicular Oocytes

Abstract: Factors affecting in vitro maturation (IVM) of minke whale (Balaenopetra acutorostrata) follicular oocytes were investigated. In experiment 1, recovery rates for oocytes from follicles of different sizes (small, 1-5 mm; medium, 6-10 mm; large, > or = 11 mm) were similar in both immature (54.7%) and mature (53.5%) females, and the follicular sizes did not affect recovery rate. Approximately half the oocytes recovered from small follicles in immature (55.5%) and mature (52.1%) whales were surrounded by at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 22 publications
2
31
0
Order By: Relevance
“…The previous IVM system for whale oocytes (Fukui et al, 1997a;Asada et al, 2001a) included approximately 310 mosmol M199 supplemented with 15-20% fetal whale serum (FWS) for the IVM medium and 96-120 h as the culture period, resulting in an approximately 30% IVM rate in fresh oocytes. The preliminary measurement of osmolarity for wFF led us to prepare a modified IVM medium in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous IVM system for whale oocytes (Fukui et al, 1997a;Asada et al, 2001a) included approximately 310 mosmol M199 supplemented with 15-20% fetal whale serum (FWS) for the IVM medium and 96-120 h as the culture period, resulting in an approximately 30% IVM rate in fresh oocytes. The preliminary measurement of osmolarity for wFF led us to prepare a modified IVM medium in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear maturation rate of minke whale oocytes is approximately 30%, even after 120 h of in vitro maturation (IVM) culture (Fukui et al, 1997a; 4 Kato Ladies Clinic, Tokyo 160-0023, Japan. 5 The Institute of Cetacean Research, Tokyo 104-0055, Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Fukui et al [14,15] attempted in vitro fertilization (IVF) of in vitro matured minke whale follicular oocytes using frozen-thawed spermatozoa, but the number of cleaved oocytes following IVF was low (5-6% of inseminated oocytes). This low cleavage rate may be due to the high proportion of morphologically abnormal spermatozoa ascertained in the present study.…”
Section: Referencesmentioning
confidence: 99%
“…The present study was conducted to produce common minke whale embryos by determining the appropriate duration for IVM (30 or 40 h: Experiment 1) and by intracytoplasmic sperm injection (ICSI) and assessment of embryonic development after IVM culture (40 or 48 h) of maturted oocytes from prepubertal and adult common minke whales (Experiment 2). Regarding the duration of IVM culture, our previous reports [1,3] showed that the nuclear maturation rate of Antarctic minke whale oocytes is approximately 30%, even after 96-120 h of IVM culture. In those studies, 15-20% fetal whale serum was incorporated into the IVM media with osmolarity of approximately 310 mOsm, but the IVM media was not supplemented with whale follicular fluid (wFF).…”
Section: Discussionmentioning
confidence: 99%
“…tudies of in vitro maturation (IVM), in vitro fertilization (IVF) and development of Antarctic minke whale (Balaenopetera bonaerensis) oocytes have previously been conducted in our laboratory [1][2][3]. Although minke whale oocytes developed to the early morula stage following IVM and IVF [3], no blastocyst stage embryos have been obtained.…”
mentioning
confidence: 99%